Design and manufacturing of mobile micro manipulation system with a compliant piezoelectric actuator based micro gripper. (April 2015) - Jain, Ravi K.; Majumder, Somajoyti; Ghosh, Bhaskar; Saha, Surajit
Highlights: Piezo bimorph actuators are used as active actuators for robotic micro assembly. A new design of manipulation system with a piezoelectric gripper is proposed. An analysis of piezoelectric micro gripper is carried out by using PD controller. Throughput analysis of manipulation system is done for finding misalignment. By developing the prototype, a novel design of micro manipulation is demonstrated. Abstract: This paper presents a new design of mobile micro manipulation system for robotic micro assembly where a compliant piezoelectric actuator based micro gripper is designed for handling the miniature parts and compensation of misalignment during peg-in-hole assembly is done because piezoelectric actuator has capability of producing the displacement in micron range and generates high force instantaneously. This adjusts the misalignment of peg during robotic micro assembly. The throughput/speed of mobile micro manipulation system is found for picking and placing the peg from one hole to next hole position. An analysis of piezoelectric actuator based micro gripper has been carried out where voltage is controlled through a proportional-derivative (PD) controller. By developing a prototype, it is demonstrated that compliant piezoelectric actuator based micro gripper is capable of handling the peg-in-hole assembly task in a mobile micro manipulation system.